Description of an enigmatic new genus and new species of Australian Orthotylinae (Insecta: Heteroptera: Miridae) associated with the plant genus Eremophila - Chin, Yee Wei; Cassis, Gerasimos (Zootaxa, 2018)
A new genus and new species of Australian orthotyline is described: Warrumiris viridis gen. nov. et. sp. nov. The species is widespread in Australia, mostly in arid and semi-arid regions of the continent. The species is associated with two species of the scrophulariaceous genus Eremophila. The species has highly autapomorphic male genitalia, with the aedeagus mostly membraneous with elongate lobal sclerites. The significance of the male genitalia is discussed.